Penentuan Derajat Luka pada Kekerasan Mekanik di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari - Juli 2019 - Kelwulan, Jessica E.; Siwu, James F.; Mallo, Johannis F. (e-CliniC, 2020)
Abstract: Determination of the degree of injury is highly important to identify the type and severity of abuse, in order to decide the level of punishment against the perpetrators. In case of living victim, a doctor may provide information regarding the injury. Type of injury, type of violence that caused the injury, and determination of injury's qualification or degree of injury, will be translated in the form of Visum et Repertum . Visum et Repertum is necessary to uncover clarity, truth and complete proof of material about a crime. It is important for a doctor to be able to determine the qualification of an injury in order to decide the severity of the sentence against the suspect. This study was aimed to determine the degree of injury in mechanical violence at Prof. Dr. R. D. Kandou Hospital Manado from January to July 2019. This was a retrospective and descriptive study using Visum et Repertum data. The results obtained 39 cases of mechanical violence. Majority of cases had sharp violence (24 cases; 61.5%), second degree injuries (29 cases; 74.4%), males (34 cases; 87%), and the age range was 15-24 years old (17 cases; 43.5%). In conclusion, most cases were males, age range of 15-24 years, had sharp violence with second degree injury.Keywords: mechanical violence, degree of injuryÂ Abstrak: Penentuan derajat luka sangat penting dilakukan untuk mengetahui jenis penganiayaan yang dilakukan dan berat ringannya ancaman hukuman terhadap pelaku. Visum et Repertum (VeR) sangat diperlukan untuk mencari kejelasan, kebenaran, dan pembuktian materil yang selengkap-lengkapnya tentang suatu tindak pidana. Kemampuan seorang dokter dalam menen-tukan kualifikasi luka sangat penting bagi pihak berwajib untuk menentukan berat ringannya hukuman terhadap tersangka. Penelitian ini bertujuan untuk mengetahui derajat luka pada kekerasan mekanik di RSUP Prof. Dr. R. D. Kandou Manado periode Januari sampai Juli 2019. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data hasil VeR. Hasil penelitian mendapatkan sebanyak 39 kasus kekerasan mekanik. Mayoritas kasus ialah akibat kekerasan tajam pada 24 kasus (61,5%), luka derajat dua pada 29 kasus (74,4%), jenis kelamin laki-laki pada 34 kasus (87%), dan rentang usia 15-24 tahun pada 17 kasus (43,5%). Simpulan penelitian ini ialah sebagian besar kasus berjenis kelamin laki-laki, rentang usia 15-24 tahun, dengan kekerasan tajam dan luka derajat dua.Kata kunci: kekerasan mekanik, derajat luka